2-Oxoamide inhibitors of cytosolic group IVA phospholipase A2 with reduced lipophilicity - Antonopoulou, G.; Magrioti, V.; Kokotou, M. G.; Nikolaou, A.; Barbayianni, E.; Mouchlis, V. D.; Dennis, E. A.; Kokotos, G. (Bioorganic and Medicinal Chemistry, 2016)
Cytosolic GIVA phospholipase A2 (GIVA cPLA2) initiates the eicosanoid pathway of inflammation and thus inhibitors of this enzyme constitute novel potential agents for the treatment of inflammatory diseases. Traditionally, GIVA cPLA2 inhibitors have suffered systemically from high lipophilicity. We have developed a variety of long chain 2-oxoamides as inhibitors of GIVA PLA2. Among them, AX048 was found to produce a potent analgesic effect. We have now reduced the lipophilicity of AX048 by replacing the long aliphatic chain with a chain containing an ether linked aromatic ring with in vitro inhibitory activities similar to AX048.